AGORA QUE SÃO ELAS... SÓ QUE NÃO: UMA ANÁLISE DA PARTICIPAÇÃO POLÍTICA DASMULHERES NO ESTADO DE MATO GROSSO DO SUL - Ellen Maria Machado Santos Fernandes (2024)
This paper aims to investigate how and whether social markers and local culture influence women's participation in politics, and how this participation (or lack thereof) impacts the lives of different categories of women, using an approach that integrates feminist and intersectional perspectives from cultural studies. To this end, a historical overview of female representation in the politics of Mato Grosso do Sul since 1977 was conducted. Social markers such as race, social class, sexual orientation, and gender identity present in the women elected to the Legislative Assembly of Mato Grosso do Sul were identified, and the laws created for women in the state were analyzed. From the perspective of Cultural Studies, the research begins with the author's reflections, which highlight the motivations for this writing. Concepts such as identity, culture, intersectionality, and feminisms are discussed, as they contribute to analyzing phenomena such as the invisibility of women in politics and the violence they face. The paper continues with a historical review of the separation of the states of Mato Grosso and Mato Grosso do Sul, introduces the politicians involved in the separatist movement, and provides a brief analysis of who they were. Subsequently, the women elected to the Legislative Assembly of Mato Grosso do Sul were analyzed based on social markers such as race, social class, sexual orientation, and gender identity. Of the eleven women elected to the ALEMS, only one is a Black woman, only two are not part of the state's traditional political families, all are cisgender, all have higher education, and only one deputy's sexual orientation is unknown, with the others being heterosexual. The laws created for women at the state level are also examined, with about 34% of all laws enacted since the state's founding occurring between April 2021 and December 2024. Finally, this paper proposes reflections on the necessary mechanisms to encourage more women to participate in public and political life. Keywords: Intersectionality; Political Representation; Cultural Studies; Social Markers; Female Invisibility.